FRAMING TAJUK RENCANA PILKADA SOLO 2015 - Yunica Rizkiyah Pratiwi, Dian Esti Nurati, Bedjo Soekarno (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2018)
ABSTRACT                This study aims to provide an overview of how Harian Joglosemar framed a fact related to the 2015 local election into an editorial during the campaign period of August 25 - December 6, 2015.                 The type of research used in this study is descriptive qualitative. Technique of collecting data using documentation method. And the data analysis technique used is Pan and Kosicki framing analysis, which is to test the editorial into syntactic, script, thematic, and rhetorical structure.               The results of this study indicate that the framing picture conducted by Harian Joglosemar is criticized but feels like a wishy-washy in writing an opinion on an editorial themed on Election of Solo 2015.Keywords: Framing analysis, Local Elections, Editorial, Joglosemar